STUDENTS THROUGH INTEGRATED LESSONS IN PRIMARY CLASSES EXPANDING ONE'S WORLD VIEW - Rustamova Davlatkhan Toyirjon qizi (Western European Studies, 2024)
The article describes the importance of integrating primary school classes and expanding the worldview of primary school students through integrated classes
Keywords: integration; method; experience; skill